Gatekeepers in regional networks of innovators - Holger Graf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The internal density of a local network is said to increase the regionspecific knowledge-stock and might lead to a comparative advantage. However, it might also lead to a lock-in situation, if local trajectories are directed towards inferior solutions. Accordingly it is argued that successful clusters are characterised by the existence of gatekeepers, i.e. actors that generate novelty by drawing on local and external knowledge. We attempt to answer questions related to the role and characteristics of gatekeepers within regional innovation systems by applying social network analysis based on patent data for four East-German regions. The regional networks appear to be significantly different with respect to the overall degree of interaction and with respect to their relative outward orientation. Concerning the characteristics of gatekeepers, we find that size does not play the major role for being a gatekeeper. It is rather absorptive capacity that matters for gatekeepers. It also shows that public research organisations serve the functions of a gatekeeper to a higher degree than private actors.
Keywords: O31; Z13; R11; 330; Innovator networks; Gatekeeper; R&D co-operation; Scientist mobility; Innovation; Forschungskooperation; Business Network; Region; Hochschulforschung; Wissenschaftler; Arbeitsmobilität; Neue Bundesländer